Lopinavir and Ritonavir have High Affinity Toward the SARS-CoV-2 S-protein Receptor-binding Domain Sequenced in Brazil - Aline Diogo Marinho; Helyson Lucas Bezerra Braz; João Alison de Moraes Silveira; Danilo Galvão Rocha; Roberta Jeane Bezerra Jorge; Geanne Matos de Andrade (BIO Integration)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), first identified in China in December 2019, rapidly spread worldwide, resulting in the coronavirus disease 2019 (COVID-19) pandemic. Understanding the structural and functional interactions between the virus and host cells is critical for developing therapeutic strategies. Methods: In this study, we employed in silico docking models to investigate the molecular interactions between the receptor-binding domain (RBD) of the SARS-CoV-2 spike glycoprotein, derived from the Brazilian genome sequence, and seven clinically approved drugs: umifenovir, darunavir, lopinavir, ritonavir, remdesivir, pirfenidone, and oseltamivir. The three-dimensional structure of the Omicron RBD model was generated through homology modeling, and potential active site cavities were predicted within the RBD structure. Results: Among the seven drugs tested, only lopinavir and ritonavir demonstrated significant binding affinities to the RBD. Lopinavir exhibited a binding affinity of −9.8 kcal/mol, forming interactions with residues PHE168, GLY167, SER176, GLN175, GLU166, LEU134, LEU137, TYR171, PHE138, LEU174, and PHE172. Ritonavir showed a binding affinity of −8.9 kcal/mol, interacting with residues ARG148, ASN130, VAL23, SER81, ASN33, PHE29, TYR33, SER31, ASN132, ALA26, ALA30, ALA34, and TYR133.Molecular dynamics simulations confirmed the stability of the complexes formed between lopinavir and ritonavir and the RBD active site. Conclusion: These findings underscore the potential of these protease inhibitors as therapeutic agents targeting the SARS-CoV-2 spike protein.